2011
DOI: 10.1103/physrevb.84.174518
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetism above the superconducting transition in underdoped La1.9Sr0.1CuO4

Abstract: The interplay between superconducting fluctuations and inhomogeneities presents a renewed interest due to recent works of different groups, which apparently support an intrinsically anomalous (beyond the conventional Gaussian-Ginzburg-Landau scenario) diamagnetism above T c in underdoped cuprates. This conclusion, mainly based in the observation of new anomalies in the isothermal magnetization curves at low-field amplitudes, is in contradiction with our earlier results in the underdoped La 1.9 Sr 0.1 CuO 4 [Ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 68 publications
7
29
0
Order By: Relevance
“…Josephson coupling between the layers leads to the onset of three-dimensional (3D) superconductivity as soon as the correlation length for superconducting order within the layers becomes sizable. 18,19 The recent observations [12][13][14][15][16] that strong superconducting correlations appear only in a regime that is reasonably close to T c are consistent with the expectation that 3D order should appear as soon as 2D superconducting correlations become substantial. 18 In fact, in a previous study of La 2−x Ba x CuO 4 (LBCO) with x = 0.095, evidence was found indicating that superconducting correlations between layers start to develop locally before superconducting correlations diverge within the layers.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Josephson coupling between the layers leads to the onset of three-dimensional (3D) superconductivity as soon as the correlation length for superconducting order within the layers becomes sizable. 18,19 The recent observations [12][13][14][15][16] that strong superconducting correlations appear only in a regime that is reasonably close to T c are consistent with the expectation that 3D order should appear as soon as 2D superconducting correlations become substantial. 18 In fact, in a previous study of La 2−x Ba x CuO 4 (LBCO) with x = 0.095, evidence was found indicating that superconducting correlations between layers start to develop locally before superconducting correlations diverge within the layers.…”
Section: Introductionsupporting
confidence: 68%
“…2-8 This work motivated theoretical suggestions 9-11 of a possible phase-disordered twodimensional (2D) superconducting state (2D vortex liquid) that might exist above T c . In contrast, recent studies of superconducting contributions to magnetoresistance 12 and low-frequency optical conductivity, 13,14 as well as further torque magnetometry studies, 15,16 indicate that strong superconducting correlations are found only within a relatively narrow range (∼10 K) above T c ; the response at higher temperatures is quite weak relative to expectations for a 2D vortex-liquid state. 17 There is general agreement that pairing interactions within the CuO 2 layers are responsible for the development of superconducting correlations in the cuprates.…”
Section: Introductionmentioning
confidence: 80%
“…1, we exclude the possibility of an asymmetric distribution of T c . 27 After obtaining T c (0), the magnetization has been measured as a function of the field (isotherm) at different temperatures: high resolution scans have been performed for several isotherms, above T c , generally by 0.03 K increments, in steps of 2 Oe, up to 1000 Oe. Additional scans at a temperature well above T c allow to determine the paramagnetic signal of the normal state, and the background contributions from the sample holder.…”
Section: Resultsmentioning
confidence: 99%
“…They find that the ratio is off by almost an order of magnitude just above T c . In a recent study of diamagnetism above T c in LSCO x = 0.1, Mosqueira et al 133 have argued that their observations can be explained by chemical disorder plus fluctuations in the pairing amplitude. At minimum, these results cast doubt on a picture of the normal state involving decoupled layers with superconductivity limited only by phase fluctuations.…”
Section: 128mentioning
confidence: 99%